2021
DOI: 10.1093/nar/gkab689
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative DNA binding mediated by KicGAS/ORF52 oligomerization allows inhibition of DNA-induced phase separation and activation of cGAS

Abstract: Cyclic GMP-AMP synthase (cGAS) is a key DNA sensor that detects aberrant cytosolic DNA arising from pathogen invasions or genotoxic stresses. Upon binding to DNA, cGAS is activated and catalyzes the synthesis of cyclic GMP-AMP (cGAMP), which induces potent antimicrobial and antitumor responses. Kaposi sarcoma-associated herpesvirus (KSHV) is a human DNA tumor virus that causes Kaposi sarcoma and several other malignancies. We previously reported that KSHV inhibitor of cGAS (KicGAS) encoded by ORF52, inhibits c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…3 B ). Previously, we have shown that single mutation of I21, L24, N28, or L31 to alanine shifted KicGAS elution positions from oligomers to dimers ( 15 ). Here we found that change of L17 to the bulky arginine residue also shifted the peak elution position from oligomers to dimers, affirming the critical roles of these residues in forming α1-mediated dimer interface ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…3 B ). Previously, we have shown that single mutation of I21, L24, N28, or L31 to alanine shifted KicGAS elution positions from oligomers to dimers ( 15 ). Here we found that change of L17 to the bulky arginine residue also shifted the peak elution position from oligomers to dimers, affirming the critical roles of these residues in forming α1-mediated dimer interface ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Although no homolog has been identified in betaherpesviruses, ORF52 is found to be structurally related to VP22 in alphaherpesviruses such as herpes simplex virus 1 (HSV-1) ( 14 ). We have reported that KicGAS and its homologs from other gammaherpesviruses inhibit cGAS activity in vitro ( 15 ). Recently, we and others found that KicGAS undergoes liquid–liquid phase separation upon binding with DNA ( 15 , 16 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations